Perceived stress in elderly stroke survivors after hospital discharge to home - Emanuella Barros dos Santos; Rosalina Aparecida Partezani Rodrigues; Sueli Marques; Octávio Marques Pontes-Neto (SciELO, 2015)
AbstractOBJECTIVETo evaluate the relationship between perceived stress and comorbidities, neurological deficit, functional independence and depressive symptoms of stroke survivors after hospital discharge.METHODCross-sectional study with 90 elderly stroke survivors. The National Institutes of Health Stroke Scale instrument, the Functional Independence Measure instrument, the Geriatric Depression Scale and the Perceived Stress Scale were used. Bivariate Pearson correlation, independent t test and multiple regression analysis were used to evaluate the relationship between perceived stress and other variables.RESULTSThe final regression model showed that higher perceived stress was related to less functional independence (p= 0.022) and more depressive symptoms (p <0.001).CONCLUSIONAt hospital discharge, interventions should be planned for the treatment of depressive symptoms and to create adaptation strategies to the reduction of functional independence, in order to reduce the stress of the survivors.